2019
DOI: 10.1126/science.aaw4911
|View full text |Cite
|
Sign up to set email alerts
|

Metastable ferroelectricity in optically strained SrTiO 3

Abstract: Fluctuating orders in solids are generally considered high-temperature precursors of broken symmetry phases. However, in some cases these fluctuations persist to zero temperature and prevent the emergence of long-range order, as for example observed in quantum spin and dipolar liquids. SrTiO3 is a quantum paraelectric in which dipolar fluctuations grow when the material is cooled, although a long-range ferroelectric order never sets in. We show that the nonlinear excitation of lattice vibrations with mid-infra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
225
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 320 publications
(234 citation statements)
references
References 50 publications
9
225
0
Order By: Relevance
“…The transient changes in optical density (denoted as ΔOD) comparing pump‐on and pump‐off conditions in the near‐infrared wavelength range ( Figure a) consist of a derivative‐like line‐shape, centered around the exciton peak at 750 nm, which oscillates above and below zero in sub‐picosecond timescales. Such periodic oscillations, which signify coherent optical phonons (COPs), have been observed in (semi)metals, [ 24 ] insulators, [ 25,26 ] and semiconductors, including MAPbI 3 itself [ 27,28 ] (but in the condition of above‐bandgap optical pumping). A key feature of using non‐resonant optical pumping here is that our data are completely free from parasitic electronic excitations; the latter usually give rise to large background in transient signals around the exciton peak due to a nonequilibrium redistribution of charge carriers near the band edge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transient changes in optical density (denoted as ΔOD) comparing pump‐on and pump‐off conditions in the near‐infrared wavelength range ( Figure a) consist of a derivative‐like line‐shape, centered around the exciton peak at 750 nm, which oscillates above and below zero in sub‐picosecond timescales. Such periodic oscillations, which signify coherent optical phonons (COPs), have been observed in (semi)metals, [ 24 ] insulators, [ 25,26 ] and semiconductors, including MAPbI 3 itself [ 27,28 ] (but in the condition of above‐bandgap optical pumping). A key feature of using non‐resonant optical pumping here is that our data are completely free from parasitic electronic excitations; the latter usually give rise to large background in transient signals around the exciton peak due to a nonequilibrium redistribution of charge carriers near the band edge.…”
Section: Resultsmentioning
confidence: 99%
“…Our observations are consistent with the formation of a rotationally disordered octahedral network in the tetragonal phase of MAPbI 3 as determined from MeV ultrafast electron diffraction experimentation, [ 11 ] as well as the spontaneous symmetry breaking in the respective cubic phase. [ 47 ] Our work sheds light on further manipulating COPs in the structurally diverse HOIPs [ 48 ] for the generation of effective magnetic fields [ 17 ] as well as the access to nonequilibrium ferroelectric phases [ 6,25,26 ] and quantum phases, [ 49,50 ] which have been previously pursued with materials such as oxide perovskites. The similarity (and difference) of the rotations of octahedra between 3D and 2D hybrid perovskites, and between inorganic and hybrid perovskites, are among the remaining questions, since it has been demonstrated that hydrogen bonding plays an important role in mediating the octahedral tilts.…”
Section: Resultsmentioning
confidence: 99%
“…[18,19] A particularly interesting case of switching occurs when the new phase is a "hidden state," i.e., a metastable and, thus, transient state of matter. Examples of such states include transient ferroelectric order in a paraelectric, [183,184] transient superconductivity-like states in superconductors in the normal-conductor phase, [185] and the heating of the spin system of a ferrimagnet without changing its total magnetization (see also Figure 26). [22] …”
Section: Condensed Mattermentioning
confidence: 99%
“…The polar phase required for exhibiting these properties can, however, be induced artificially by modification of the lattice. Large biaxial strain, light pulses, and elemental substitutions can convert SrTiO 3 into a ferroelectric material, whereas strain gradients can induce a polarization via the flexoelectric effect or oxygen vacancies migration . Electron diffraction measurements furthermore show that the top TiO 2 surface layer of SrTiO 3 undergoes surface relaxation and oxygen ions move outward from the surface relative to the titanium ions, leading to a polarization of this layer .…”
mentioning
confidence: 99%